2008
DOI: 10.1093/eurheartj/ehn172
|View full text |Cite
|
Sign up to set email alerts
|

Association of mitral annular calcification and aortic valve morphology: a substudy of the aortic stenosis progression observation measuring effects of rosuvastatin (ASTRONOMER) study

Abstract: In patients with asymptomatic mild to moderate AS, MAC is more prevalent in those individuals with tricuspid AV, independent of age, and systolic blood pressure. Whether the degree of MAC may be a surrogate for atherosclerosis, and predict the subset of patients who will respond to statin therapy in preventing the progression of AS, remains to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
7

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 23 publications
0
28
0
7
Order By: Relevance
“…Our finding that MAC is less prevalent in the patients with bicuspid AVS coincides to the previous studies. Jassal and associates [21] showed that, in patients with asymptomatic mild to moderate AVS, those with tricuspid aortic valves had more extensive MAC compared to those with bicuspid aortic valves, using transthoracic echocardiography. Roberts and colleagues [22] reported that MAC was less frequent in those with unicuspid and bicuspid valves than in those with tricuspid valves (19,20, and 61 %) at necropsy of 260 patients with AVS without operative therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding that MAC is less prevalent in the patients with bicuspid AVS coincides to the previous studies. Jassal and associates [21] showed that, in patients with asymptomatic mild to moderate AVS, those with tricuspid aortic valves had more extensive MAC compared to those with bicuspid aortic valves, using transthoracic echocardiography. Roberts and colleagues [22] reported that MAC was less frequent in those with unicuspid and bicuspid valves than in those with tricuspid valves (19,20, and 61 %) at necropsy of 260 patients with AVS without operative therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The aortic valve annulus diameter (mm) was measured using transesophageal echocardiography (TEE) in the long-axis view. Aortic valve calcification relied on visualization of bright echoes at the base of the aortic valve leaflets using TEE, and was graded as mildly calcified when calcification appeared as small isolated spots, moderately calcified when multiple larger spots were present, and heavily calcified when extensive thickening and calcification of all cusps was seen (8). The thickness of both the noncoronary cusp (NCC) and the right coronary cusp was measured in the long-axis view using TEE.…”
Section: Methodsmentioning
confidence: 99%
“…Jassal et al 27 reported the close relationship between mitral annular calcification and aortic valve calcification in patients with aortic stenosis. We did not assess the effects of mitral annular calcification, but the relationship between mitral regurgitation and progression of early-stage CAVD may be partly explained by the previous finding.…”
Section: Prognostic Factors For Progression Of Early-stage Cavdmentioning
confidence: 99%